Chile : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that over the past two decades, Chile has adhered to a sound and consistent policy framework. During 2000-03, the actual overall balance of the central government registered a deficit of just below 1 percent of GDP. Since the beginning of 2004, economic activity has picked up, in the context of a favorable external environment. The global economic recovery has helped boost export demand, particularly copper, the price of which has nearly doubled since end-2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet